"Helsinki sind wir". Sozialistische Transnationalität im Literaturbetrieb der DDR - Zajas, Paweł (Taylor & Francis Group, 2023)
The forced integration of European socialist states following WWII is usually viewed as a history of political misunderstandings and genuine social failures. From the early modernism and avant-garde periods onwards, socialism was also a common experience for the whole of East and Central Europe. Since the late 1950s, the densifying network of relations among culture departments of socialist parties, culture ministries of individual countries, writer associations, publishers or literary journals has resulted in thus far unknown transnational literature circula- tion. This article analyzes the transnational links between the GDR literary system and the literatures and literary institutions of the European Eastern Bloc. The paper aims to discuss two specific research questions. First, the international literature published in the GDR is examined statistically and regarding the prevail- ing concepts and practices of transnationality. Second, the transnationally net- worked places of socialist literature planning are presented. Documents preserved in East German archives form the basis for the research.
Keywords: East German publishing field; East European book market; Transnationalism and East Europe; Sociology of literature; Circulation of literature; Literary transfer